2017
DOI: 10.1371/journal.pone.0168226
|View full text |Cite
|
Sign up to set email alerts
|

Weight Perturbation Alters Leptin Signal Transduction in a Region-Specific Manner throughout the Brain

Abstract: Diet-induced obesity (DIO) resulting from consumption of a high fat diet (HFD) attenuates normal neuronal responses to leptin and may contribute to the metabolic defense of an acquired higher body weight in humans; the molecular bases for the persistence of this defense are unknown. We measured the responses of 23 brain regions to exogenous leptin in 4 different groups of weight- and/or diet-perturbed mice. Responses to leptin were assessed by quantifying pSTAT3 levels in brain nuclei 30 minutes following 3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Therefore, these responses do not differ qualitatively or quantitatively among individuals with and without obesity. What differs among individuals is the threshold, and therefore leptin signal transduction is dependent upon an individual's "usual weight" and any ongoing or previous negative energy balance (78).…”
Section: Neuromolecular Mechanisms Of Energy Homeostasismentioning
confidence: 99%
“…Therefore, these responses do not differ qualitatively or quantitatively among individuals with and without obesity. What differs among individuals is the threshold, and therefore leptin signal transduction is dependent upon an individual's "usual weight" and any ongoing or previous negative energy balance (78).…”
Section: Neuromolecular Mechanisms Of Energy Homeostasismentioning
confidence: 99%
“…What differs between individuals with and without obesity is the threshold. Therefore leptin signal transduction is dependent upon an individual's "usual weight" and any ongoing or previous negative energy balance (Morabito et al, 2017).…”
Section: Leptin Signaling Is Non-linearmentioning
confidence: 99%
“…In particular, decreasing the dietary fat content in mice fed with HFD for 20 weeks reverses obesity and hypothalamic leptin sensitivity in the ARH after 7 weeks of diet switch (Enriori et al 2007). Another study showed that 12 weeks of low-fat diet after 30 weeks of DIO not only decreases body weight and leptinaemia to values similar to lean mice but also recovers leptin-induced pSTAT3 levels in some brain regions to a greater extent than energy restriction (Morabito et al 2017). However, ARH and DMH do not recover leptin sensitivity neither with energy restriction nor with dietary switch (Morabito et al 2017).…”
Section: Reversion Of Leptin Resistance In Obesity Modelsmentioning
confidence: 99%
“…Fasting-induced decrease in leptinaemia is partly regulated by sympathetic outflow to the white adipose tissue regulating leptin biosynthesis and secretion (Caron et al 2018). Energy restriction also reduces leptinaemia and restores leptin-induced pSTAT3 response in several brain regions including VMH (Morabito et al 2017). Additionally, diet switch from HFD to regular chow reverses leptin resistance in some DIO models.…”
Section: Reversion Of Leptin Resistance In Obesity Modelsmentioning
confidence: 99%
See 1 more Smart Citation